The Prevalence of Antibiotic and Toothpaste Sensitivity found in Oral Streptococcal Isolates in Healthy Individuals in the Okada Community of Nigeria - Okwu, Maureen U; Mitsan, Olley (Makara Journal of Health Research, 2017)
Background: This study aimed to determine the prevalence, antibiotic, and toothpaste sensitivity of oral streptococcal isolates in healthy individuals in the Okada community of Nigeria. Methods: Oral samples were collected from 230 volunteers and were subjected to standard microbiological tests. Antibacterial sensitivity tests were carried out on the streptococcal isolates that were obtained using a disk diffusion technique, and eight kinds of toothpaste (A-H) were screened for their antibacterial effects on Streptococcus mutans (S. mutans). Results: The prevalence of oral streptococci found in this study was 26.1% and the predominant species was S. salivarius (13.9%). S. salivarius was highly resistant to cloxacillin (100%) and Augmentin (96.9%), whilst resistance to gentamicin and erythromycin was low at 21.9% and 3.1% respectively. S. mutans were completely sensitive to gentamicin whilst resistance to erythromycin was 33.3%. The entire Streptococcus species showed the lowest resistance to erythromycin (20.0%), followed by gentamicin (31.7%). At 100 mg/mL all toothpaste samples had antibacterial effects on S. mutans. At 50 mg/mL all samples except toothpastes G and H inhibited the bacterium. Toothpastes A and E had the lowest minimum inhibitory concentration of 25 mg/mL. Conclusions: Toothpastes A and E were the most effective toothpastes of the eight assessed in this study.